(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article examines the traditional musical creativity of the Uzbek people, with particular emphasis on its historical periods and stylistic characteristics. It analyzes the evolution of folk music styles in relation to socio-cultural developments and regional influences. The study aims to reveal how various musical forms reflect the national identity, worldview, and aesthetic values of the Uzbek people. The article also discusses the importance of preserving these unique stylistic traditions in the context of modern cultural transformations.